Bacillus velezensis strain HYEB5-6 as a potential biocontrol agent against anthracnose on Euonymus japonicus. Issue 5 (4th May 2017) - Huang, Lin; Li, Qiu-Cheng; Hou, Yao; Li, Guo-Qian; Yang, Ji-Yun; Li, De-Wei; Ye, Jian-Ren
ABSTRACT: Anthracnose is a foliar disease of the Euonymus shrub caused by Colletotrichum gloeosporioides . In this study, the bacterium HYEB5-6 was isolated from inside one-year-old branches of healthy Euonymus japonicus and showed significant antifungal activities against various phytopathogenic fungi, including C. gloeosporioides s.s. HYCG2-3, in dual culture experiments. The HYEB5-6 isolate significantly decreased lesion diameter and disease index caused by C. gloeosporioides inoculation on detached leaves of E. japonicus. The effects of HYEB5-6 metabolites on the invading structure of the fungus were investigated. Bacterial metabolites inhibited conidial germination, the growth of the germ tube and appressorium formation, possibly through protease and glucanase of HYEB5-6 by managing the mycelial cell wall. The HYEB5-6 isolate also produced a massive biofilm, which might facilitate leaf colonisation. These results indicate that HYEB5-6 has the potential for use as a biological control agent against C. gloeosporioides . The HYEB5-6 isolate was identified as Bacillus velezensis based on its biochemical characteristics and its 16S rRNA gene sequence.